Plasma nontargeted metabolomics study of H1N1 and H3N2 influenza in children - Li, Yaping; Li, Jiaxin; Li, Ting; Liu, Chenrui; Du, Jiayi; Li, Yuxin; Chen, Yuan; Zhang, Yufeng; Wang, Xiaoyan; Wang, Xinyu; Jia, Xiaoli; Deng, Huiling (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThis study used a nontargeted metabolomic approach to investigate small molecular metabolites in the peripheral blood of pediatric patients with influenza. By comparing these metabolites with those in healthy children, potential biomarkers for the early detection and diagnosis of influenza were explored.MethodsPlasma samples were collected from 47 children with H1N1 influenza, 40 with H3N2 influenza, and 40 healthy controls at Xi’an Children’s Hospital, Xi’an Jiaotong University Second Affiliated Hospital, and Xi’an Central Hospital between May and September 2023. Nontargeted metabolomic detection and analysis were performed.ResultsIn the H1N1 group, 14 glycerophospholipid metabolites were significantly altered compared to controls, with 11 (78.5%) markedly downregulated. These downregulated metabolites showed negative correlations with inflammatory markers, including white blood cell (WBC) count, neutrophils, C-reactive protein (CRP), and Procalcitonin (PCT), whereas the upregulated metabolite PC(P-18:1(9Z)/16:0) showed positive correlations with validation markers. In the H3N2 group, 12 glycerophospholipid metabolites were significantly altered, with 9 being downregulated. The downregulated LysoPC(20:0/0:0) showed a positive correlation with alanine aminotransferase (ALT) but a negative correlation with WBC count, while the upregulated metabolite LysoPA(18:1(9Z)0:0) correlated positively with ALT, aspartate aminotransferase (AST), and lactate dehydrogenase (LDH).ConclusionsDistinct metabolomic profiles were identified in pediatric H1N1 and H3N2 influenza cases compared to healthy controls. Specific glycerophospholipid metabolites were closely associated with inflammatory and liver function markers, highlighting their potential as biomarkers for disease monitoring and early diagnosis.